Testicular Regression Syndrome: a case report - Vinhas, Christiana de Freitas; Felipe-Silva, Aloísio; Rocha, Ricardo Frank Coelho da (Autopsy and Case Reports, 2012)
Testicular Regression Syndrome (TRS) is defined as the absence or an incomplete development of the testis of varying degrees in 46XY patients with normal external genitalia. The prevalence ranges from 3-20% of cases previously diagnosed as cryptorchidism. We report the case of a 7-year-old boy who underwent surgical exploration with an initial diagnosis of cryptorchidism. Testicular structure was not identified and presumed testicular remnants were sent for histological analysis. The histological sections showed a fibrovascular nodule, structures of the spermatic cord and calcification, supporting the diagnosis of TRS